The Influence of Career Advancement on Employee Performance and Job Satisfaction (A Case Study at PT Bank Akasia Mas) - Satoto, Ayu Audina; Dwianto, Agung Surya (LPPM Institut Pendidikan Nusantara Global, 2025)
In the dynamic competition of the banking industry, career acceleration has become a crucial strategy in human resource management to enhance employee performance and job satisfaction. This study aims to analyze the influence of career acceleration on employee performance and job satisfaction at PT Bank Akasia Mas. A quantitative approach by an explanatory research design was employed, involving 154 participants selected through purposive sampling. Data were collected utilizing validated questionnaires, complemented by interviews and observations. Regression analysis results reveal that career acceleration significantly affects both performance (R² = 0.31) and job satisfaction (R² = 0.39). When organizational culture was included, the R² value improved to 0.48, highlighting its strong moderating role. The study also reveals structural disparities in access to career enhancement programs across divisions, negatively affecting job satisfaction. Moreover, the influence of career acceleration on performance is largely mediated by job satisfaction. These outcomes emphasize the importance of a fair, structured, and competency-based career enhancement system, along by the reinforcement of an inclusive organizational culture. This study gives both practical and theoretical contributions to comprehending career dynamics in Indonesia’s banking sector and offers strategic recommendations for improving organizational productivity through influenceive career management.